Prejudice : causes, consequences and cures. (Del Mar, Calif. : CRM/McGraw-Hill Films, 1983)
This film focuses on research findings and their implications for dealing with prejudice against women and specific racial, national and ethnic groups.
Keywords: Prejudices and antipathies